One wintry night - Graham, Ruth Bell.; Watson, Richard Jesse (Grand Rapids, Mich. : Baker Books, 1994)
Retells the Christmas story in a contemporary setting, beginning with creation and closing with Christ's resurrection.
Keywords: Jesus Christ -- Nativity -- Juvenile literature; Christmas -- Juvenile literature; Jesus Christ; Christmas; Jesus Christ; Christmas; Nativity of Jesus Christ; Juvenile works